A relação entre o retrofit e a satisfação do usuário: Estudo de caso em uma empresa do Vale dos Sinos - Schreiber, Isabela Franco (Universidade do Vale do Rio dos Sinos, 2017)
Retrofit is a technique that is growing in Brazil, as it contributes to an improvement in the performance and expansion lifetime build, as well as to bring together issues of environmental, social and economic sustainability, with aesthetic and functional aspects, increasing the quality of the environment, in consolidated buildings that need to change your use. The feeling of comfort and well-being is achieved by the physical characteristics of each environment, such as layout, temperature, lighting, ventilation, humidity, external view, ergonomics and furniture, and companies seek to offer pleasant spaces and work environments that meet the needs of your users approaching the relationship between the employees, and consequently increase the productivity. In this context, this work, case study, the main objective of is to evaluate the adopted strategies, joining sustainable and economic solutions to the project and execution of a retrofit, in a commercial building, in the city of São Leopoldo, in Rio Grande do Sul, using current aesthetic elements and corporate, to improve users satisfaction. The study was carried out in stages, beginning with the surveys, which included visits for analysis of the existing building and application of a post-occupation evaluation (POE) questionnaire, followed by identification of the elements that could be modified, associated with the characteristics of the existing building and without representing large structural changes, to define the design guidelines, in accordance with the requirements of the LEED certification for new construction & major renovation, and Commercial interiors. This work also presents the projects of the new proposal developed, as well as images of the execution of the work until its conclusion, when a new POE questionnaire was applied, as way to verify the project solutions. The comparison between the questionnaires demonstrates an increase in user satisfaction levels regarding comfort and well-being, after the application of sustainable strategies, and the importance of the POE for some project definitions.
Keywords: Retrofit; Arquitetura corporativa; Qualidade no ambiente de trabalho; Avaliação pós-ocupação; Satisfação do usuário; Corporate architecture; Quality in the work environment; Post-occupation evaluation; User satisfaction; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo